Peripheral–conscious energy–efficient scheduling for weakly hard real–time systems. (4th December 2014) - Niu, Linwei; Quan, Gang
In this paper, we study the problem of reducing the energy consumption for a weakly hard real–time system. The weakly hard real–time system is modelled by the (m, k)–constraints, which require that at least m out of any k consecutive jobs of a task meet their deadlines. Since the system energy is consumed not only by the processor alone but also in a large part by other peripheral devices, we first propose a static approach, with the specifications of peripheral devices taken into consideration, to partition the jobs into mandatory/optional jobs to achieve the dual goals of (m, k)–guarantee and overall energy minimisation. Based on that, we present a dynamic scheduling algorithm that adopts preemption control technique and dynamic mandatory/optional partitioning strategy to reduce the energy consumption of the whole system dynamically. Our approach can effectively minimise the system–wide energy consumption and guarantee the (m, k)–deadlines at the same time. The novelty and effectiveness of our techniques are demonstrated through extensive simulation studies.